Bad Kitty : kitten trouble - Bruel, Nick (New York : Roaring Brook Press, 2018)
When a nearby cat shelter is destroyed, Bad Kitty's family decides to foster some of the displaced kittens.
Kirkus Review, November 2018
2.2
K-3
GN560L
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Animal shelters -- Juvenile fiction; Cats -- Juvenile fiction; Humorous stories; Bad Kitty -- (Fictitious character from Nick Bruel) -- Fiction; Animal shelters -- Fiction; Cats -- Fiction; Humorous stories; Humorous fiction; Comics (Graphic works); Graphic novels